2019
DOI: 10.1016/j.fsi.2019.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon responses of common carp strains with different levels of resistance to koi herpesvirus disease during infection with CyHV-3 or SVCV

Abstract: 22Highlights 24 1. Differences in mortality rates during SVCV and CyHV-3 infections were recorded in carp 25 strains. 26 2. The higher resistance of the Rop strain was related to lower virus load and replication. 27 3. The magnitude of type I IFN response was not positively correlated with survival. 28 4. CyHV-3 has an ability to limit IFN response induced by sensing viral DNA by cells. 29 30 Abstract 34 Carp from breeding strains with different genetic background present diverse levels of 35 resistance to vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Previous transcriptomic studies in susceptible CyHV-3 infected common carp, shared our observation of a wide response that is mainly immune related [36, 37]. More specifically, IFN-mediated response to CyHV-3 infection has been reported recently also for other carp strains with variable survival levels [38]. The IFN response in fish, similarly to mammals, acts as an important part of innate anti-viral immunity [46] and thus, induction of this pathway is not suprising.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous transcriptomic studies in susceptible CyHV-3 infected common carp, shared our observation of a wide response that is mainly immune related [36, 37]. More specifically, IFN-mediated response to CyHV-3 infection has been reported recently also for other carp strains with variable survival levels [38]. The IFN response in fish, similarly to mammals, acts as an important part of innate anti-viral immunity [46] and thus, induction of this pathway is not suprising.…”
Section: Discussionsupporting
confidence: 70%
“…Since the two fish types are considerably different, both genetically and phenotypically [18, 35], it was not surprising to find many transcriptional differences (840 DEGs) at day 0 (S0/R0) driven by basal genetic variation. As reported before, CyHV-3 infects both fish types, mortalities of susceptible fish start around day 8 post-infection and by day 6 post infection, viral loads in susceptible fish are significantly higher than in resistant fish [18, 38]. Thus, day 4 post-infection was chosen here to study the gene expression differences that can potentially explain why resistant fish more effectively control the viral load and survive.…”
Section: Discussionmentioning
confidence: 99%
“…The common carp is characterized with the economic importance and genetic diversity in the genome. The genetic diversity of common carp strains leads to distinct phenotypes in body color, body shape, scale pattern, growth rate, and response and tolerance to pathogens ( Nielsen et al, 2010 ; Odegard et al, 2010 ; Jiang et al, 2014 ; Xu et al, 2014b ; Adamek et al, 2019 ), offers an attractive model to dissect the genetic basis of the economic traits. The genetic background of fish also plays pivotal roles in shaping the transcriptional responses to environmental stresses, which in turn determines the resistance of the animals to the subsequent lethal level challenges of the same stress ( De Nadal et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single nucleotide polymorphism (SNP) in IL-10a along with elevated expression of IL-12 p35, IFN ɑβ and TLR 9 contributes to this resistance [ 35 ]. This was not the case, however, in a study in which the immune responses in different carp strains with different levels of resistance to KHVD were evaluated: it was found that the resistant Ropsha (Rop) and Amur wild (AS) strains had a higher survival rate than Prerov scale (PS) and koi strains, but the levels of IFN type 1 did not correlate with this resistance phenotype [ 36 ].…”
Section: Discussionmentioning
confidence: 99%